2006
DOI: 10.1002/jmv.20584
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two rapid influenza A/B test kits with reference methods showing high specificity and sensitivity for influenza A infection

Abstract: The rapid detection of influenza viruses is important for forming preventative strategies, directing initiation of anti-viral therapy, detecting potential avian influenza viruses, and excluding influenza-like pathogens, such as SARS. The ImmunoCard STAT! Flu A and B Plus test (Meridian Bioscience, Cincinnati, OH) is a new point of care (POC) test utilizing influenza-specific monoclonal antibodies for rapid diagnosis. The performance of this assay was compared to the established POC Binax NowFlu A and NowFlu B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 10 publications
1
21
1
1
Order By: Relevance
“…Two recent studies showed that BinaxNOW has 71% to 80% sensitivity for detecting influenza A and only 37% to 47% sensitivity for detecting influenza B in patients, compared with viral culture, indirect immunofluorescence (IFA), and real-time RT-PCR (13,14). In another retrospective study with frozen nasopharyngeal specimens from adult and pediatric patients, the authors reported sensitivities of 62.2% and 54.5% by BinaxNOW for influenza A and influenza B, respectively, compared with real-time RT-PCR (15).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies showed that BinaxNOW has 71% to 80% sensitivity for detecting influenza A and only 37% to 47% sensitivity for detecting influenza B in patients, compared with viral culture, indirect immunofluorescence (IFA), and real-time RT-PCR (13,14). In another retrospective study with frozen nasopharyngeal specimens from adult and pediatric patients, the authors reported sensitivities of 62.2% and 54.5% by BinaxNOW for influenza A and influenza B, respectively, compared with real-time RT-PCR (15).…”
Section: Discussionmentioning
confidence: 99%
“…Combining the results of nasal and throat swabs did not change the sensitivity (74.0% versus 73.6%), but a larger number of patients were positive compared to the number when nasal swabs alone were used (177 versus 159). Sensitivities for influenza viruses A and B were similar, whereas previous POC test evaluations have reported lower sensitivities for influenza virus B (30 to 50%) than influenza virus A (6,7,9,14).…”
Section: Discussionmentioning
confidence: 50%
“…Virus culturing and/or IFT were predominantly used as reference method. Sensitivity of these rapid tests can be compared to that of IFT and EIA [29,30].…”
Section: Virus Culturementioning
confidence: 99%